Ischemic Stroke and Risk of Venous Thromboembolism in the General Population: The Tromsø Study - Balteskard Rinde, Ludvig; Småbrekke, Birgit; Mathiesen, Ellisiv B.; Løchen, Maja-Lisa; Njølstad, Inger; Mathiesen Hald, Erin; Wilsgaard, Tom; Brækkan, Sigrid Kufaas; Hansen, John-Bjarne (Journal of the American Heart Association, 2016)
Source at https://doi.org/10.1161/JAHA.116.004311. This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License , which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made. Background - Even though clinical data support a relation between ischemic stroke and venous thromboembolism (VTE), the strength and time dependence of the association remain to be settled at the population level. We therefore aimed to investigate the association between ischemic stroke and VTE in a prospective population-based cohort. Methods and Results - Participants (n=30 002) were recruited from 3 surveys of the Tromsø study (conducted in 1994–1995, 2001, and 2007–2008) and followed through 2010. All incident events of ischemic stroke and VTE during follow-up were recorded. Cox-regression models with age as time scale and ischemic stroke as a time-dependent variable were used to calculate hazard ratios (HR) of VTE adjusted for cardiovascular risk factors. During a median follow-up time of 15.7 years, 1360 participants developed ischemic stroke and 722 had a VTE. The risk of VTE was highest the first month (HR 19.7; 95% CI, 10.1–38.5) and from 1 to 3 months after the stroke (HR 10.6; 95% CI 5.0–22.5), but declined rapidly thereafter. The risk estimates were approximately the same for deep vein thrombosis (HR 19.1; 95% CI, 7.8–38.5), and pulmonary embolism (HR 20.2; 95% CI, 7.4–55.1). Stroke was associated with higher risk for provoked (HR 22.6; 95% CI, 12.5–40.9) than unprovoked VTE (HR 7.4; 95% CI, 2.7–20.1) the first 3 months. Conclusions - The risk of VTE increased during the first 3 months after an ischemic stroke. The particularly high risk of provoked VTE suggests that additional predisposing factors, such as immobilization, potentiate the VTE risk in patients with ischemic stroke.